Polyamino-Isoprenyl Derivatives as Antibiotic Adjuvants and Motility Inhibitors for Bordetella bronchiseptica Porcine Pulmonary Infection Treatment - Borselli, Diane; Brunel, Jean Michel; Gorgé, Olivier; Bolla, Jean Michel (Frontiers in Microbiology, 2019)
The spreading of multidrug resistant bacteria and the lack of novel antibiotic molecules are leaving clinicians and veterinarians with very limited options to treat bacterial infections, especially those caused by Gram-negative pathogens. To reduce the selection of antibiotic resistance mechanisms and their transfer to human pathogens, veterinary pharmaceutical companies have dramatically decreased the number of used antibiotics. Among all the investigated alternate solutions, chemosensitizers, which decrease the amount of the used drugs appears to be one of the most promising strategy. In this study, we reported that polyamino-isoprenyl derivatives can potentiate florfenicol activity against veterinary sensitive reference strains as well as clinical isolates. These molecules induce inner membrane depolarization and subsequently inhibit efflux pumps by collapsing the proton motive force (PMF). Considering that B. bronchiseptica rotor flagellum is highly PMF dependent and that flagellar motility represents an important factor involved in colonization, we monitored the swimming and swarming motilities of bacteria and showed a strong inhibition in the presence of the lead selected compound. Taken together, our results suggest that this class of molecules are able to increase treatment efficacy and decrease drug consumption.